PECULIARITIES AND DIFFICULTIES IN DARK TOURISM MANAG EMENT AND CONSUMPTION - Kavolėlytė, Inga (Acta Museologica Lithuanica, 2015)
This research mainly focuses on the consumption of dark tourism destinations, particularly destinations related with genocide. Dark tourism combines very contrary ideas and means, balances between historical representation, touristic activities and psychological, ethical and managerial aspects. This sector suffers from contradictions in defining activities; it is difficult to explain and understand its development through demand and supply dimensions, through the practical usage of traumatic events, consumerism, equity and controllability sides. The main issue analysed is that sites of atrocity face a commodification of people, monuments and services versus the actual value and message of a destination.
Keywords: Genocide; Holocaust; death; trauma; contested heritage; consumer culture; dark tourism